IMPLICATIONS OF POPULISM ON PUBLIC POLICIES: THE INCREASE IN THE PENSION OF DEPRIVATION OF LIBERTY (ANTI-CRIME PACKAGE) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Populism has played a prominent role in recent years, even though it is not a current activity, as it has already marked the past, it has gained momentum and voice through easy and simplified speeches that move the population. Because populism can influence public policies, the theme of this article is punitive populism and the custodial sentence. As a thematic delimitation, the legislative changes promoted by Law No. 13,694/2019 will be addressed, in particular the increase in the maximum penalty for the custodial sentence in a closed regime. To this end, aiming to relate populism with public policies that have increased Brazilian punishments/legislation, the general objective of the study, as well as a guiding question, is the following: how does populism and the increase in the custodial sentence, through the change legislation of the Anti-Crime Package, could they be related? What are the possible impacts of the measure, of the legislative resurgence, on society? Divided into three parts, it aims, first, to address populism and its influence on public policies; in the second moment, deal with changing the maximum penalty for serving a custodial sentence, in a closed regime, to 40 (forty) years; and, finally, to focus on exposing the possible impacts of the relationship between populism and legislative changes in society, as well as the stigmatization and marginalization of a select public. As for the methodology, deductive reasoning is used, approaching and intertwining the ideas of populism with the resurgence of punishments, with data collection in works by scholars who study the subject and in Brazilian laws.